The Influence Mechanism of Knowledge Heterogeneity of Venture Capital Syndication on Innovation Performance of Entrepreneurial Firms: Evidence from China. (8th October 2022) - Zhang, Huiying; Li, Xiangchun; Liu, Meng
Abstract : Venture capital syndication (VCS), an investment model, is gaining increasing attention. This paper uses a new perspective on knowledge transfer to explore the influence mechanism of knowledge heterogeneity in VCS on the innovation performance (IP) of entrepreneurial firms. We use firm-year panel data from the Shenzhen Stock Exchange for 2000–2017 and find that the knowledge heterogeneity of VCS includes, at least, management knowledge heterogeneity, investment knowledge heterogeneity, and technical knowledge heterogeneity. In particular, management knowledge heterogeneity and technical knowledge heterogeneity positively affect the IP of entrepreneurial firms. We further find that the intellectual capital (IC) of entrepreneurial firms mediates these positive relationships. Moreover, the equity concentration of VCS positively moderates the relationship between knowledge heterogeneity and IP and negatively moderates the relationship between knowledge heterogeneity and IC. This paper provides a new theoretical explanation of the relationship between VCS and IP of entrepreneurial firms from a knowledge transfer perspective and explores the impact paths of this relationship.